A metabolomic serum signature from nonhuman primates treated with a radiation countermeasure, gamma-tocotrienol, and exposed to ionizing radiation - Pannkuk, Evan L. (Health Phys, 2018)
The search for and development of radiation countermeasures to treat acute lethal radiation injury has been underway for the past six decades, resulting in the identification of multiple classes of radiation countermeasures. However, to date, only granulocyte colony-stimulating factor (G-CSF, Neupogen) and PEGylated G-CSF (Neulasta) have been approved by the United States Food and Drug Administration (US FDA) for the treatment of hematopoietic acute radiation syndrome (H-ARS). Gamma-tocotrienol (GT3) has demonstrated radioprotective efficacy in murine and nonhuman primate (NHP) models. Currently, this agent is under advanced development as a radioprotector, and we are trying to identify its efficacy biomarkers. In this study, we analyzed global metabolomic changes using ultra-performance liquid chromatography (UPLC) quadrupole time-of-flight mass spectrometry (QTOF-MS). Our pilot study using 16 NHPs (eight NHPs each in GT3- and vehicle-treated groups), with samples obtained from GT3-treated and irradiated NHPs, demonstrates several metabolites that are altered after irradiation, including compounds involved in fatty acid-β oxidation, purine catabolism, and amino acid metabolism. The machine-learning algorithm, Random Forest, separated control, irradiated GT3-treated, and irradiated vehicle-treated NHPs at 12 h and 24 h as evident in a multidimensional scaling plot. Primary metabolites validated included carnitine/acylcarnitines, amino acids, creatine, and xanthine. Overall, GT3-administration reduced high fluctuations in serum metabolite levels, suggesting an overall beneficial effect on animals exposed to radiation. This initial assessment also highlights the utility of metabolomics to determine underlying physiological mechanisms responsible for the radioprotective efficacy of GT3.